Time and space in words and music ; proceedings of the 1st Conference of the Word and Music Association Forum, Dortmund, November 4 - 6, 2010 - Dunkel, Mario; Petermann, Emily; Sauerwald, Burkhard (Proceedings of the ... conference of the Word and Music Association Forum, 2012)
Addressing a range of music examples and texts, the 15 essays in this volume explore the interaction between both conceptions of time and space and the intermedial relationship between words and music. This intermedial experimentation may serve to adopt the spatio-temporal attributes of the other medium or to comment on a form's own mediality. It has much to say about processes of literary and musical composition and reception, the role of tradition and intertextuality, and the medial constellation in which these works situate themselves.
Literaturangaben
Keywords: Aufsatzsammlung; Konferenzschrift -- 2010 -- Dortmund; Geschichte; Interdisziplinarität; Musik; Literatur